Cephalocyclus iohannisgabrielis (Coleoptera: Scarabaeidae: Aphodiinae), a new species from Oaxaca, Mexico - Dellacasa, Marco; Arriaga-Jiménez, Alfonsina (Zootaxa, 2020)
The genus Cephalocyclus Dellacasa, Gordon & Dellacasa, 1998 (Coleoptera: Scarabaeidae: Aphodiinae: Aphodiini) was created for 10 species distributed in southern United States of America and Mesoamerica. Subsequently, 14 species were described or added to this genus (Dellacasa et al. 2000, 2007, 2011, 2013; Deloya & Ibáñez-Bernal 2000; Minor et al. 2015). A.A.-J. collected a large series of specimens from Oaxaca (Mexico) belonging to a new species of Cephalocyclus described here. The specimens of this new species came from “El Cerro del Aguila” in the Mixteca Region, between 2800–3250 m. All specimens were collected with pitfall traps baited with human excrement.